Connection between basic values and emigration attitudes of Russian youth - Zhanagul Zh. Romasheva; Olga V. Kalinichenko; Ivan V. Malyshev (Saratov State University, 2021)
The ambiguity and inconsistency of the data on the connection between emigration attitudes and metavalues spurs the research on the relation between emigration attitudes and basic values. Hence, the problem of studying the deterministic character of youth attitudes to emigration is seen as of relevance. The purpose of this research is to determine the nature of the connection between basic values and emigration attitudes. Hypotheses: 1. The basic values that make up metavalues act as the predictors of emigration attitudes. 2. The basic values constituting the contrastive metavalues of Preservation and Openness to Change are simultaneously connected with emigration attitudes, and the nature of their connections is different. 3. The basic values constituting the metavalue of Self-Affirmation have a positive correlation with emigration attitudes. The study is carried out on a sample of respondents (N = 646) aged 17 to 35, including 78% (504) of women. The research applies the "Scales of Migration Attitudes" (S. A. Kuznetsova, I. Yu. Kuznetsov, A. V. Feshchenko) modified to study emigration attitudes. The study also uses PVQ-21 ESS7 versions of the questionnaire measuring individual values (Sh. Schwartz) which enables to document the degree of expression of values. Finally, the research makes use of the method of multiple linear regression analysis. The results show that the attitude of the subject is the most pronounced one among all other components of emigration attitudes (the attitude of the loved ones, the expectations of the loved ones). Basic values have a major impact on the revealed connections between emigration attitudes and metavalues. For example, the values of tradition and security have a negative correlation with the metavalue of Preservation. The values of stimulation have a positive correlation with the metavalue of Openness to Change. The values of power have a positive correlation with the metavalue of Self-Affirmation. Evidently, young adults are more likely to plan to emigrate due to their personal attitudes and motives rather than to those of their close environment. Attitudes towards emigration are expressed by those young adults who: 1) are less focused on traditions and customs but appreciate security; 2) strive to enrich their lives with new sensations and emotions; 3) appreciate material well-being. The results of the study reveal the factors contributing to the emergence of attitudes to emigration in young adults. The results of the study can be used to predict international mobility of young adults. Additionally, they are of importance for the psychological work with potential emigrants.